2019
DOI: 10.2196/13173
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Heart Failure Apps to Promote Self-Care: Systematic App Search

Abstract: BackgroundHeart failure (HF) is a chronic disease that affects over 1% of Canadians and at least 26 million people worldwide. With the continued rise in disease prevalence and an aging population, HF-related costs are expected to create a significant economic burden. Many mobile health (mHealth) apps have been developed to help support patients’ self-care in the home setting, but it is unclear if they are suited to the needs or capabilities of older adults.ObjectiveThis study aimed to identify HF apps and eval… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 34 publications
(59 reference statements)
3
32
0
Order By: Relevance
“…It is in line with the results of a recent systematic review that showed evidence that HF patients can improve their QoL by promoting their self-care behaviors [13]. Previous studies suggested that self-management interventions like education, support, and guidance can improve the QoL in HF patients with diverse delivery methods such as face-to-face interaction, telephonic conversation, accessing websites, mobile applications [27][28][29][30].…”
Section: Discussionsupporting
confidence: 73%
“…It is in line with the results of a recent systematic review that showed evidence that HF patients can improve their QoL by promoting their self-care behaviors [13]. Previous studies suggested that self-management interventions like education, support, and guidance can improve the QoL in HF patients with diverse delivery methods such as face-to-face interaction, telephonic conversation, accessing websites, mobile applications [27][28][29][30].…”
Section: Discussionsupporting
confidence: 73%
“…Our participants' descriptions of an ideal future HF app is one that would detect and alert the user to symptoms and signs of a worsening condition. Although this capacity is lacking in current HF apps, this kind of app has the potential to promote better self-care for HF patients [40] and involves the HF patient's perspective. Furthermore, having HF patients use telemonitoring or a structured telephone support system from home has an impact on HF patients' quality of life [41], improves their HF symptoms and signs [41,42], and reduces mortality [42], readmissions, and hospitalization [43].…”
Section: Discussionmentioning
confidence: 99%
“…Smartphones and mobile health apps have the potential for bettering patient engagement and self-management. While there are a number of commercially available smartphone heart failure apps, few have been designed by clinicians or specifically designed to address heart failure self-management; only 41% had weight management features [7]. Even fewer have published their methodology and feasibility studies [8,9] in peer-reviewed journals.…”
Section: Introductionmentioning
confidence: 99%